Literature review of flexibility attributes: A flexibility framework for software developing organization. Issue 9 (15th February 2018) - Nurdiani, Indira; Börstler, Jürgen; Fricker, Samuel A.
Abstract: Software developing organizations strive to achieve flexibility to maintain a competitive advantage. There is no common understanding of what characterize flexibility for a software organization beyond the scope of the software product. Without a common understanding, it is difficult to evaluate the degrees of flexibility of software development approaches. The aim of this literature review is to collect attributes that characterize flexibility. The collected attributes are consolidated into a flexibility framework with 3 main attributes: properties of change, flexibility perspectives, and flexibility enablers. The resulting flexibility framework is then used to evaluate Agile and Lean practices. The evaluation shows that Agile and Lean practices address many flexibility attributes. However, some attributes are not addressed, such as infrastructure flexibility and strategic flexibility. On the basis of our evaluation, the classifications of flexibility attributes that we present in this paper could be used to aid software organization flexibility evaluation. Abstract : The paper presents a flexibility framework with 3 main attributes: properties of change, flexibility perspectives, and flexibility enablers. The resulting flexibility framework is then used to evaluate Agile and Lean practices. The evaluation shows that Agile and Lean practices address many flexibility attributes, but not all.